The formation of traditional music and regional pop music community in popular social media - Shafa’atussara Silahudin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Traditional music and regional pop music are two music genres in Pahang. Both music genres provide the cultural meanings to the Pahang people. They have shared similar characteristics consisting of traditional elements inherited from the past. Quatrains of pantun and Malay traditional proverbs are adopted as sung texts in both music genres. Interestingly, the implementation of Pahang spoken language (Pahang dialect), one of the Malay dialects in Peninsula Malaysia, is an additional characteristic of regional pop music. Both music genres incorporate tradition and modern elements of tempo, melody and music structure. In both music genres, the combinations of modern and traditional musical instruments are used. Music practitioners, Roslan Madun and vocal group Anok Semantan represent traditional and regional pop, respectively. To investigate community formation through the genres, three methodological components are used: participant-observation, interviewing, and textual analysis. The findings suggest that community in traditional music (in this regard, syair songs) is formed through syair concert, and the formation of virtual community in media social of Facebook as continuity of the concert community. Regional pop music, on the other hand, forms the community on the popular music web of YouTube. The findings also expose different in attitudes, motivations and practices between traditional and regional pop communities.